Bird assemblage structure in the Desert Puna in areas with different disturbance activity of a subterranean herbivorous rodent - Andino, Natalia del Pilar (2024)
Herbivorous subterranean rodents, such as Ctenomys mendocinus (tuco-tuco), have a significant impact on vegetation cover and composition. This study aimed to examine the indirect influence of tuco-tucos on bird populations and assemblages in the southernmost region of the desert Puna. In a shrub-steppe community, at an altitude of between 3,000 and 3,100 m.a.s.l., bird surveys were conducted from February 2001 to October 2004. Transects of 50 m in length and 40 m in width were established: 56 located in highly disturbed patches and 53 in patches with low disturbance by tuco-tucos. Our results show that areas with higher disturbance by tuco-tucos are associated with a decrease in bird abundance (93 individuals in disturbed areas vs. 226 in undisturbed areas) and lower species richness (6 species in disturbed areas vs. 11 in undisturbed areas).